PEMBAGIAN ASET HARTA BENDA SEBELUM MENINGGAL DUNIA PERSPEKTIF SADD AL-DHARĪ’AH - Dimas Maulana Jaka Perdana; Muhammad Muhammad (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The distribution of family property is often a sensitive issue because it has the potential to create disputes among heirs, particularly after the death of the parents. In social practice, the distribution of property during the owner’s lifetime is frequently used as an alternative mechanism to maintain family harmony and prevent future inheritance conflicts. This phenomenon is also found in the community of Sogaan Village, Pakuniran District, Probolinggo Regency, where hibah is practiced as a means of distributing assets before death. This study aims to analyze the practice of distributing assets prior to death and to examine it from the perspective of sadd al-dharī‘ah in Islamic law. The study employs an empirical juridical method with a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and were analyzed descriptively and analytically. The findings reveal that the people of Sogaan Village regard hibah as an alternative method of property distribution to prevent disputes among heirs after the death of the parents. The practice is carried out through family deliberation and is based on considerations of benefit and the condition of each recipient. From the perspective of Islamic law, this practice is substantively more appropriate to be categorized as hibah rather than inheritance, since it is conducted while the property owner is still alive. The analysis based on the concept of sadd al-dharī‘ah shows that the practice may be understood as a preventive measure to close the possibility of mafsadah in the form of family conflict. Therefore, the distribution of assets during one’s lifetime in Sogaan Village may be considered consistent with the objectives of Islamic law in realizing maslahah, as long as it is carried out voluntarily, transparently, mutually agreed upon, and in accordance with the principle of justice